Ordinary risks and accepted fictions: how contrasting and competing priorities work in risk assessment and mental health care planning. (17th June 2016) - Coffey, Michael; Cohen, Rachel; Faulkner, Alison; Hannigan, Ben; Simpson, Alan; Barlow, Sally
Abstract: Background: Communication and information sharing are considered crucial to recovery‐focused mental health services. Effective mental health care planning and coordination includes assessment and management of risk and safety. Objective: Using data from our cross‐national mixed‐method study of care planning and coordination, we examined what patients, family members and workers say about risk assessment and management and explored the contents of care plans. Design: Thematic analysis of qualitative research interviews ( n = 117) with patients, family members and workers, across four English and two Welsh National Health Service sites. Care plans were reviewed ( n = 33) using a structured template. Findings: Participants have contrasting priorities in relation to risk. Patients see benefit in discussions about risk, but cast the process as a worker priority that may lead to loss of liberty. Relationships with workers are key to family members and patients; however, worker claims of involving people in the care planning process do not extend to risk assessment and management procedures for fear of causing upset. Workers locate risk as coming from the person rather than social or environmental factors, are risk averse and appear to prioritize the procedural aspects of assessment. Conclusions: Despite limitations, risk assessment is treated as legitimate work by professionals. Risk assessment practice operates as a type of fiction in which poor predictive ability and fear of consequences are accepted in the interests of normative certainty by all parties. As a consequence, risk adverse options are encouraged by workers and patients steered away from opportunities for ordinary risks thereby hindering the mobilization of their strengths and abilities.